Rotating charged black holes in EMS theory: shadow studies and constraints from EHT observations - Odil Yunusov; Javlon Rayimbaev; Furkat Sarikulov; Muhammad Zahid; Ahmadjon Abdujabbarov; Zdeněk Stuchlík (European Physical Journal C: Particles and Fields)
Abstract One of the possible ways to test gravity theories and get constraints on parameters of a gravity theory and a black hole is based on studies of black hole shadow applying Event Horizon Telescope (EHT) data from the shadow sizes of M87* and Sgr A*. In this sense, we study the shadow of rotating charged black holes in Einstein–Maxwell scalar (EMS) theory. First, we obtain a rotating EMS black hole solution and analyze the horizon properties. We derive the effective potential for the circular motion of photons along null geodesics around the rotating black hole and obtain the black hole shadow using celestial coordinates. The effects of the black charge and spin and EMS theory parameters on the shape of the black hole shadow, its radius, and distortion parameters are analyzed in detail. We have obtained upper and lower limits for spin and black hole charges of Sgr A* and M87* using their shadow size for various values of EMS parameters. Lastly, we computed and examined the standard shadow radius, equatorial, and polar quasinormal modes using the geometric-optic relationship between the parameters of the quasinormal mode and the conserved values along the geodesics.